Analisis Kesulitan dalam Pembelajaran Pjok terhadap Siswa Inklusi di SDN Margorejo III Surabaya - Cavita, Risna Dhea; Sunanto Sunanto; Akhwani Akhwani; M. Sukron Djazilan (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The background of the difficulties in learning PJOK for inclusion students isdifferent in each inclusion student, low grade students tend to have difficulties in terms of material but can still follow for practice while high grade students have difficulties in terms of practice but easy in terms of material. The purpose of the study was to analyze the difficulties in learning PJOK for inclusion students at SDN Margorejo III Surabaya. This research method uses a type of descriptive qualitative research. Using observation, interviews and documentation. The number of samples was 53 inclusion students as research objects. Data collection instruments in this study, using question sheets for interviews and documentation. The results showed that the difficulties experienced by teachers at SDN Margorejo III Surabaya were about the difficulty of PJOK teachers training their motors, the difficulty of PJOK teachers facing the mood of inclusion students, the difficulty of PJOK teachers practicing sports in the field and difficulty delivering material. In general, the research conducted to analyze the difficulties experienced by teachers at SDN Margorejo III Surabaya is about the difficulty of PJOK teachers training their motors, the difficulty of PJOK teachers facing the mood of inclusion students, the difficulty of PJOK teachers in practicing sports in the field and the difficulty of delivering material.